Adopting circular economy in construction: a review - Rao, Preethi Amrut; Rahman, Md Motiar; Duraman, Saiful Baharin (Frontiers in Built Environment, 2025)
Global development is integral to construction activities that consume enormous amounts of natural resources, of which a considerable part is wasted during the construction and demolition phases. Only a small part of such construction and demolition waste is recovered and recycled, and the rest goes to landfills and dumpsites, containing a high volume of recoverable and reusable materials and components, causing environmental hazards and depleting natural resources. This occurs due to the practice of linear economic model in construction. By contrast, the circular economy (CE) approach can potentially offer an effective solution for this issue, through its long-lasting and standardized design with reduced resource input; and extensive reuse and recycling of resources, products and components. However, CE is not being widely practiced. As such, this study was designed to investigate why CE is not being widely practiced, and what needs to be done for its wider adoption. As the beginning, a systematic literature review extracted 32 motivators, 35 challenges and 31 strategies. Further analysis clustered these three groups of factors into eight focus areas of: legal and regulatory framework; knowledge, education and training; infrastructure, technology and innovation; awareness promotion and support; collaboration and information sharing; standardization; circular business model and positive finance and economics. Finally, a conceptual framework is presented, for wider adoption of CE and sustainability assessment and reporting, in construction. The outcomes are expected to provide guidance and indication to policy and decision-makers on what needs to be done for wider adoption of CE in construction.